2015
DOI: 10.1186/s13321-015-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

AtomicChargeCalculator: interactive web-based calculation of atomic charges in large biomolecular complexes and drug-like molecules

Abstract: BackgroundPartial atomic charges are a well-established concept, useful in understanding and modeling the chemical behavior of molecules, from simple compounds, to large biomolecular complexes with many reactive sites.Results This paper introduces AtomicChargeCalculator (ACC), a web-based application for the calculation and analysis of atomic charges which respond to changes in molecular conformation and chemical environment. ACC relies on an empirical method to rapidly compute atomic charges with accuracy com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 86 publications
2
48
0
Order By: Relevance
“…Verstraelen et al have claimed that for the development of ab initio derived force fields, atomic charges must be computed from electronic structure computations, such that (i) they accurately describe the molecular electrostatic potential and (ii) they are transferable to the force field application of interest [130]. Ionescu and coworkers [190] argued that partial atomic charges are a well-established concept and are very useful in understanding and modeling the chemical reactivity behavior of molecules, ranging from simple compounds, to crystals, to large drug-like molecules, to biomacromolecular complexes with hundreds of thousands of atoms. Hamad et al [191] found that knowledge of atomic charges on specific systems is important, and that they are useful in gaining insight into metal-organic frameworks (MOFs).…”
Section: Is the Concept Of Atomic Charge Meaningful?mentioning
confidence: 99%
“…Verstraelen et al have claimed that for the development of ab initio derived force fields, atomic charges must be computed from electronic structure computations, such that (i) they accurately describe the molecular electrostatic potential and (ii) they are transferable to the force field application of interest [130]. Ionescu and coworkers [190] argued that partial atomic charges are a well-established concept and are very useful in understanding and modeling the chemical reactivity behavior of molecules, ranging from simple compounds, to crystals, to large drug-like molecules, to biomacromolecular complexes with hundreds of thousands of atoms. Hamad et al [191] found that knowledge of atomic charges on specific systems is important, and that they are useful in gaining insight into metal-organic frameworks (MOFs).…”
Section: Is the Concept Of Atomic Charge Meaningful?mentioning
confidence: 99%
“…In each iteration of stage I, the classical MD segment was started from the snapshot with the highest content of secondary structure sampled during the preceding segment of perturbed MD; if no suitable structure could be identified (i.e., no residues were involved in a secondary structure element), the last snapshot of the perturbed MD segment was used as a starting frame for the subsequent segment of classical MD. Before starting perturbed MD, the native charges from the topology file were replaced with non-native charges, which were computed using the Electronegativity Equalization Method 26 implemented in ACC 71 . In the ACC calculation, the total charge was +1 e, −1 e, and 0 e for the Trp-cage, Aβ17-34, and (AAQAA)3, respectively; no solvent was included in the ACC calculation; the parameter set EX-NPA_6-31Gd_PCM was used 27 , and the option Full EEM was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…The initial 3D quercetin conformation was determined using HyperChem 8.0 (Hypercube, Inc., Gainesville, FL, USA), and its charge was set to the most abundant anionic and fluorescent anion species at pH 7.4, taken from Dangles et al [37]. The quercetin partial charges were calculated according to Ionescu et al [53]. A grid map of size 80 × 80 × 80 Å was generated with a 0.375 Å spacing centered on the coordinates of the side-chain nitrogen in Trp214 in Sudlow's site I in subdomain IIA by the AutoGrid program [52], and then the Lamarckian genetic algorithm (LGA) [54] was applied.…”
Section: Docking Studiesmentioning
confidence: 99%